Emerging alternatives in megaproject management: A case study of the pioneering LNG energy project in Cyprus - Andrey Afanasiev; Savvas Constantinou; Stelios Georgiou; Olga Kandinskaia (The Central European Review of Economics and Management (CEREM), 2024)
Aim: The aim of this paper is to contribute to the project management studies by systematization, generalization, and structurization of information about an energy megaproject in Cyprus, as well as to provide practical insights and guidance on how megaprojects can be started and managed in other locations. Design / Research methods: By its research design, this paper is a case study analysis. The major focus of the case study is the decision-making process of the LNG energy megaproject in Cyprus. Conclusions/findings: Even positive emerging alternatives, like the discovery of newly natural resources, can delay a megaproject instead of speeding up it due to impact on the decision-making process and reassessment of the value creation. Originality/value of the article: The LNG energy megaproject in Cyprus provides a unique example of an emerging strategic alternative which requires a reassessment of the initial approach and its comparison in terms of value creation with the newly appeared opportunity.
Keywords: G31; H43; P28; 330; emerging alternatives; ESG; LNG energy project; megaprojects; project management; risk assessment; value creation